PENINGKATAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) MELALUI PEMUPUKAN LIMBAH TERNAK PADA LAHAN PASANG SURUT - Hawayanti, Erni; Palmasari, Berliana (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2018)
This study aims to analyze and obtain the best type and level of fertilization of livestock waste on the growth and production of shallots (Allium ascalonicum L.) on tidal land. on tidal land. This research has been carried out on farmers' land in Telang Jaya Village, Muara Telang District, Banyuasin Regency, South Sumatra Province, from August to January 2018. This study used a Split-plot design with 9 repeated treatment combinations 3 times and 5 sample plants from each treatment. The treatment factor for Type of Livestock Waste (O) consisting of O1 = cattle waste, O2 = Goat livestock waste, O3 = Chicken livestock waste and Red Onion Fertilization Rate (T) consists of T1 = 5 tons / ha, T2 = 10 tons / ha, T3 = 15 tons / ha. The variables observed are 1. Plant height (cm) 2. Number of  leaves (strands) 3. Number of tubers per clump (cloves) 5. Fresh weight per clump (g) 6. Bulb weight per plot (kg). The results showed that the treatment of chicken manure and doses of 10 tons / hectare produced the highest growth and production in tuber weight / clump on red onion (Allium ascalonicum L.) plants on tidal land, ie 13.31 tons / hectare